User Experience Evaluation in Virtual Museum Tours: A Scoping Review (2014-2024) - Araújo, Calíope Corrêa de; Nunes, Fátima de Lourdes dos Santos; Teixeira, João Marcelo Xavier Natário (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Virtual museum tours are crucial tools for expanding accessibility to cultural heritage, offering immersive experiences that overcome geographic and socioeconomic barriers. Despite several studies on user experience (UX) in this context, a comprehensive compilation of these works is lacking, which is vital for identifying research opportunities and guiding advancements. This review consolidates findings from 20 studies published between 2014 and 2024, following four phases: identification, screening, eligibility, and inclusion. Studies were selected from seven databases, including ACM Digital Library and ScienceDirect. The main objective was to identify the most commonly used methodological approaches and the existing gaps in the literature. The review highlights the predominance of standardized questionnaires, qualitative interviews, behavioral observations, and structural equation modeling emerged as primary UX evaluation methods. The findings highlight usability, engagement, accessibility, and the mitigation of physical discomfort as critical for user satisfaction, emphasizing the need for standardized evaluation methods and broader user inclusion. Future research should focus on unified frameworks and expanding studies to underrepresented regions. Advancing technology is expected to foster more inclusive, accessible, and engaging virtual experiences, promoting democratized access to cultural heritage.